Content matters! The effects of TikTok (Douyin) short video content on flow experience, trust, and purchase intention from the signaling theory perspective - Ng, Siew Imm; Kamal Basha, Norazlyn; Qiao, Lin Ling; Ying, Xia Li (University Malaysia Sarawak, 2024)
Short video commerce has become increasingly popular among consumers, creating a novel environment to reshape the consumer shopping experience. However, limited research have focused on the consumer shopping experience in the TikTok (Douyin) context. Combining stimulus-organism-response (S-O-R) model with the signaling theory, this study focuses on how the TikTok short video content attributes function as signals that can drive flow experience and trust, thus inducing buying behaviors. A survey of 322 Generation Y TikTok shoppers in mainland China was conducted. The results of the PLS-SEM study revealed that content diagnosticity, vicarious expression, online reviews, and authenticity significantly influenced the flow experience. However, online reviews and authenticity did not positively impact on consumer trust. Lastly, flow experience and trust were found to mediate the influence of short video content on purchase intention. These findings offer theoretical and practical insights, emphasizing the significance of short video content.